M E D I A: DESIGNING A MODEL OF IFL LEARNING MATERIALS FOR FOREIGN WORKERS - Niknik Mediyawati; Ninuk Lustyantie; Emzir Emzir (LPMPP Universitas Negeri Yogyakarta, 2019)
Communication gap because of linguistic difference and unavailability of specific learning materials become a problem of foreign workers working in Indonesia. A specific research that develops IFL learning materials to overcome these problems is needed. This study aims to develop and improve the quality of available IFL materials. Methodology used here is Research and Development, combining quantitative-qualitative approaches. The result of this study is: 1) M E D I A as a new framework learning materials with humanistic approach that presents multicultural domestic foreign workers’ characters bound by a shared narrative on linguistic problems within business communication realm; and 2) M E D I A as mnemonic technique to embody those multicultural characters and values into teaching materials’ books namely BIPA Business Communication. High-scoring of colleagues’ evaluation and experts’ validation confirms that the IFL is highly recommended to use. Having been implemented in large-scale class through Indonesian Proficiency Test (IPT), current study achieves effectively testing result which shows that this model of IFL learning materials is effective to use because it helps to improve the language skill of students.